Character - Smiles, Samuel, 1812-1904 (Salt Lake City, UT : Project Gutenberg, 2001)
"Character" by Samuel Smiles is a philosophical treatise written during the mid-19th century. The work addresses the fundamental role of character in personal and societal development, emphasizing the importance of moral integrity, duty, and the cultivation of virtues in shaping both individuals and communities. The text highlights various historical figures and examples to illustrate how character influences one's actions and the broader societal fabric. The opening of the book lays a strong foundation for its central themes by exploring the essence of character and its impact on human life. Smiles begins with poignant quotes from renowned thinkers before proceeding to articulate his views on the supremacy of character over intellect or wealth. He asserts that genuine excellence arises from the moral fiber of individuals and stresses that true greatness lies in fulfilling one's duties satisfactorily, regardless of one's station in life. Throughout this portion, the reader is introduced to the idea that personal conduct in everyday situations reflects one's character more accurately than grand achievements, invoking examples of well-known figures to reinforce these principles. (This is an automatically generated summary.)
Release date is 2001-03-01
Produced by Sean Hackett, and David Widger
Keywords: Conduct of life; Character